Phylogenomic analysis does not support a classic but controversial hypothesis of progenitor‐derivative origins for the serpentine endemic Clarkia franciscana. (1st June 2022) - Sianta, Shelley A.; Kay, Kathleen M.
Abstract: Budding speciation involves isolation of marginal populations at the periphery of a species range and is thought to be a prominent mode of speciation in organisms with low dispersal and/or strong local adaptation among populations. Budding speciation is typically evidenced by abutting, asymmetric ranges of ecologically divergent sister species and low genetic diversity in putative budded species. Yet these indirect patterns may be unreliable, instead caused by postspeciation processes such as range or demographic shifts. Nested phylogenetic relationships provide the most conclusive evidence of budding speciation. A putative case of budding speciation in the serpentine endemic Clarkia franciscana and two closely related widespread congeners was studied by Harlan Lewis, Peter Raven, Leslie Gottlieb, and others over a 20‐year period, yet the origin of C. franciscana remains controversial. Here, we reinvestigate this system with phylogenomic analyses to determine whether C. franciscana is a recently derived budded species, phylogenetically nested within one of the other two putative progenitor species. In contrast to the hypothesized pattern of relatedness among the three Clarkia species, we find no evidence for recent budding speciation. Instead, the data suggest the three species diverged simultaneously. We urge caution in using contemporary range patterns to infer geographic modes of speciation.